Survey of Preventable Disaster Deaths at Medical Institutions in Areas Affected by the Great East Japan Earthquake: Retrospective Survey of Medical Institutions in Miyagi Prefecture. Issue 5 (9th May 2017) - Yamanouchi, Satoshi; Sasaki, Hiroyuki; Kondo, Hisayoshi; Mase, Tomohiko; Otomo, Yasuhiro; Koido, Yuichi; Kushimoto, Shigeki
Abstract: Introduction: In 2015, the authors reported the results of a preliminary investigation of preventable disaster deaths (PDDs) at medical institutions in areas affected by the Great East Japan Earthquake (2011). This initial survey considered only disaster base hospitals (DBHs) and hospitals that had experienced at least 20 patient deaths in Miyagi Prefecture (Japan); therefore, hospitals that experienced fewer than 20 patient deaths were not investigated. This was an additional study to the previous survey to better reflect PDD at hospitals across the entire prefecture. Method: Of the 147 hospitals in Miyagi Prefecture, the 14 DBHs and 82 non-DBHs that agreed to participate were included in an on-site survey. A database was created based on the medical records of 1, 243 patient deaths that occurred between March 11, 2011 and April 1, 2011, followed by determination of their status as PDDs. Results: A total of 125 cases of PDD were identified among the patients surveyed. The rate of PDD was significantly higher at coastal hospitals than inland hospitals (17.3% versus 6.3%; P<.001). Preventable disaster deaths in non-DBHs were most numerous in facilities with few general beds, especially among patients hospitalized before the disaster in hospitals with fewer than 100 beds. Categorized by area, the most frequent causes of PDD were: insufficient medical resources, disrupted lifelines, delayed medical intervention, and deteriorated environmental conditions in homes and emergency shelters in coastal areas; and were delayed medical intervention and disrupted lifelines in inland areas. Categorized by hospital function, the most frequent causes were: delayed medical intervention, deteriorated environmental conditions in homes and emergency shelters, and insufficient medical resources at DBHs; while those at non-DBHs were disrupted lifelines, insufficient medical resources, delayed medical intervention, and lack of capacity for transport within the area. Conclusion: Preventable disaster death at medical institutions in areas affected by the Great East Japan Earthquake occurred mainly at coastal hospitals with insufficient medical resources, disrupted lifelines, delayed medical intervention, and deteriorated environmental conditions in homes and emergency shelters constituting the main contributing factors. Preventing PDD, in addition to strengthening organizational support and functional enhancement of DBHs, calls for the development of business continuity plans (BCPs) for medical facilities in directly affected areas, including non-DBHs. S Yamanouchi, H Sasaki, H Kondo, T Mase, Y Otomo, Y Koido, S Kushimoto .Survey of preventable disaster deaths at medical institutions in areas affected by the Great East Japan Earthquake: retrospective survey of medical institutions in Miyagi Prefecture .Prehosp Disaster Med .2017 ;32 (5 ):515 –522 .